2020
DOI: 10.1105/tpc.20.00115
|View full text |Cite
|
Sign up to set email alerts
|

Long-Read cDNA Sequencing Enables a “Gene-Like” Transcript Annotation of Transposable Elements

Abstract: A transcript-based annotation of transposable elements allows for reduced bioinformatic complexity and direct hypothesis testing of previously challenging regions of the genome.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 48 publications
5
60
0
Order By: Relevance
“…Although some tools have been developed so far to overcome these obstacles, most of the lncRNA identification pipelines still ignore ambiguously mapped reads [ 24 , 25 ]. Thus, long-read sequencing technologies provide a great opportunity for transcriptome exploration, including the identification of transcribed repeats (e.g., transposable elements) or repeat-related transcripts [ 26 ]. Moreover, Panda and Slotkin [ 26 ] showed that by using Nanopore long cDNA reads, it is even possible to trace the expression of individual TEs from multicopy families in Arabidopsis and maize.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some tools have been developed so far to overcome these obstacles, most of the lncRNA identification pipelines still ignore ambiguously mapped reads [ 24 , 25 ]. Thus, long-read sequencing technologies provide a great opportunity for transcriptome exploration, including the identification of transcribed repeats (e.g., transposable elements) or repeat-related transcripts [ 26 ]. Moreover, Panda and Slotkin [ 26 ] showed that by using Nanopore long cDNA reads, it is even possible to trace the expression of individual TEs from multicopy families in Arabidopsis and maize.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, long-read sequencing technologies provide a great opportunity for transcriptome exploration, including the identification of transcribed repeats (e.g., transposable elements) or repeat-related transcripts [ 26 ]. Moreover, Panda and Slotkin [ 26 ] showed that by using Nanopore long cDNA reads, it is even possible to trace the expression of individual TEs from multicopy families in Arabidopsis and maize. The application of long-read technologies to the exploration of the lncRNA repertoire in plants has been demonstrated for several plant species, including Oryza sativa L. ssp.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of previous studies of RTE expression used short RNAseq reads to identify expressed RTEs. Although RNAseq is a robust method of gene expression analysis, it is challenging to estimate retrotransposon expression using this approach [8,25,48]. Our first attempt to detect expressed RTEs by RNAseq led to the identification of >300 expressed RTEs.…”
Section: Rnaseq and Nanopore Rna Sequencing Are Complementary Approacmentioning
confidence: 99%
“…No algorithms exist that reconstruct entire TE transcripts. Nanopore RNA (cDNA) sequencing has recently been applied to plant TE "gene-like" annotation in an Arabidopsis mutant defective in the main TE-silencing pathways [25]. The nanopore cDNA reads from Arabidopsis and the PacBio reads from maize can be exploited to precisely determine TE transcripts and transcription features, including transcription start sites and poly-A tail length.…”
Section: Introductionmentioning
confidence: 99%
“…In a new study, Panda and Slotkin used Oxford Nanopore Technology long-read sequencing of cDNAs to establish a transcriptbased annotation of TEs in Arabidopsis thaliana (Panda and Slotkin, 2020) ( Figure 1A). To expose TE transcripts for sequencing and annotation, the authors used a combination of Arabidopsis mutants compromised in multiple layers of TE silencing.…”
Section: In the Transcripts: Long-read Transcriptomics Enables A Novementioning
confidence: 99%